A transgenic-cloned pig model expressing non-fluorescent modified Plum - NAGAYA, Masaki (J Reprod Dev, 2016)
Genetically modified pigs that express fluorescent proteins such as green and red fluorescent proteins have become indispensable biomedical research tools in recent years. Cell or tissue transplantation studies using fluorescent markers should be conducted, wherein the xeno-antigenicity of the fluorescent proteins does not affect engraftment or graft survival. Thus, we aimed to create a transgenic (Tg)-cloned pig that was immunologically tolerant to fluorescent protein antigens. In the present study, we generated a Tg-cloned pig harboring a derivative of Plum modified by a single amino acid substitution in the chromophore. The cells and tissues of this Tg-cloned pig expressing the modified Plum (mPlum) did not fluoresce. However, western blot and immunohistochemistry analyses clearly showed that the mPlum had the same antigenicity as Plum. Thus, we have obtained primary proof of principle for creating a cloned pig that is immunologically tolerant to fluorescent protein antigens.